(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
By analyzing the main characters in some novels of Philip Roth, you can highlight elements of a speech both metafictional and performative. These are tested with a focus on communicative intentions of the author as to those core themes that are imposed.